Tensile bond strength of hydroxyethyl methacrylate (HEMA) bonding agent to bovine dentine surface at various humidity - Adioro Soetojo (Dental Journal (Majalah Kedokteran Gigi), 2006)
One factor that make bonding agent adhere to dentine surface maximally is the humidity condition around the dentine surface. The best bond strength between bonding agent with dentine surface is depending on the moist surface. It mean that the dentine surface should neither too dry or wet. The objective of this research is to know the tensile bond strength of hydroxyethyl methacrylate (HEMA) bonding agent to bovine dentine surface at various humidity. The bovine dentine was grounded to give flat surface, which was then etched with 37% phosphoric acid for 15 seconds. Dentine was washed with 20 ml water and dried with blot dry technique. The dentine, except the control group, was placed in a desiccator for one hour at difference humidity. Dentin was removed from desiccator, then covered with bonding agent and put into tensile tool plunger. Self-cured acrylic resin was applied on this bonding agent layer, which was placed on opposite-plunger. After 24 hours, tensile bond strength was measured with Autograph instrument. Data was statistically analyzed with One-Way ANOVA at 95% confidence level, continued with LSD test. Results of this study showed that 60%–90% humidity gave produce the lower of tensile bond strength of bonding agent to dentine surface (p ≤ 0.05). In conclusion, the treatment in 60% humidity gave the greatest tensile bond strength.